THE OWN REVENUES OF THE UNITED TERRITORIAL COMMUNITIES’ BUDGETS: COMPOSITION, STRUCTURE AND TENDENCIES - Shchur, R.I.; Svirskyi , V.S.; Plets, I.I. (The actual problems of regional economy development, 2019)
The paper describes the structure and reveals tendencies of formation of own revenues of budgets of the united territorial communities in the conditions of decentralization. The peculiarities of forming the own revenues of the budgets of the united territorial communities are considered. The analysis of own revenues of the budgets of the united territorial communities for 2017-2018 showed that the income tax has the largest share in the total structure of own income of the united territorial communities. Detailed analysis of the local budgets own revenues showed that the rate of increase of local taxes and fees is the highest in the local budgets of the united territorial communities for 2017-2018. These results indicate an increase of participation and interest of local governments in increasing the revenues of the budgets of the united territorial communities, the implementation of measures to finding of the reserves of their revenues and improving the efficiency of fiscal administration of taxes and fees. The set of the budget innovations regarding the revenues of the budgets of the united territorial communities is characterized: 3% of rent payment for the use of subsoil (for the extraction of oil, natural gas and gas condensate), 100% of the single tax that is paid by the payers of the fourth group (farmers), revenues of the budgets of the united territorial communities from the approval of the license terms as to economic activity, conducting of issuance and arranging of lotteries. The authors substantiate the directions of expansion of qualitative and quantitative composition of own budget revenues of the united territorial communities.